Optimization of Stunting Prevention Education Programs in Improving The Quality of Parenting and Nutritional Balance of Children - Khansa Dinah Trisnawati; Muthia Lestari; Widi Syawali; Firda Alfira Muklis; Asep Kurnia Jayadinata; Idat Muqadas; Gia Nikawanti (TAAWUN, 2025)
This Community Service Activity aims to increase the understanding and awareness of parents in Margamukti Village regarding the importance of proper parenting patterns and balanced nutritional health in early childhood. The research method used is a qualitative approach with observation data collection, interviews, and documentation. The study's results showed increased public knowledge and awareness of the importance of proper parenting patterns and balanced nutrition to prevent stunting. The interactive discussion opened space for participants to share experiences and find solutions to various challenges faced in maintaining children's health and nutrition. Overall, this activity succeeded in achieving its goal of providing education and awareness to the community, which is expected to be the first step in reducing stunting rates in Margamukti Village. This community service activity emphasizes the importance of the involvement of various parties, including pregnant women, breastfeeding mothers, posyandu cadres, and the community, in supporting stunting prevention. With a qualitative approach focusing on counseling and in-depth information delivery, this program can help reduce the risk of stunting in the target area. The impact is not only on children's health but also on improving the quality of human resources in the future.